Agents of change political philosophy in practice - Laurence, Ben (Harvard University Press, 2021)
"Ben Laurence argues for a political philosophy that unifies theory and practice in pursuit of change. He shows that the task of political philosophy is not complete until the political philosopher asks the question "What is to be done?" and deliberates about the answer with agents of change"--